Синтез, фізико-хімічні та біологічні властивості 2-[(3-R-2-оксо-2Н-[1,2,4]триазино[2,3-c]хіназолін-6-іл)тіо]оцтових кислот та їх похідних. - Носуленко, Інна Степанівна; Nosulenko, Inna Stepanivna (Запорізький державний медичний університет, 2015)
The strategy of the search of the novel chemotherapeutic agents which assume the using of in silico screening methods was elaborated and implemented in presented work. As a part of presented work series of 2-[(3-R-8-R1-9-R2-10-R3- 2-oxo-2Н-[1,2,4]triazino-[2,3-c]quinazolin-6-yl)thio]acetic acids and their derivatives were synthesized, their spectral characteristics physicochemical and biological were described. The potential and limitations of 3-R-8-R1-9-R2-10-R3-6-thioxo-6,7-dihydro-2H-[1,2,4]triazino[2,3-c]quinazolin-2-ones and their S-potassium salts modification aimed to the introduction of known “pharmacophores” to mentioned heterocycle system via acetamide “linker” group were estimated. Based on the results of biological assays the prospectivity of the searching of novel anticancer, antifungal, antivirus, actoprotective and cerebroprotective agents among studied compounds was shown and “lead-compounds” were identified. The synthetic methods applied to the synthesis of 3-R-8-R1-9-R2-10-R3-2-оксо-2Н-[1,2,4]-triazino[2,3-с]quinazoline-6-thiolates and corresponding thiones using halogen-containing 6-R-3-(2-amino-3-R1-4-R2-5-R3-phenyl)-1,2,4-triazine-5-ones as initial compounds were modified for a fist time. It was shown that presence of halogen in molecule significantly effect to the duration of reaction. Halogen-containing 2-[(3-R-8-R1-9-R2-10-R3-2-oxo-2H-[1,2,4]triazino[2,3-c]-quinazolin-6-yl)thio]acetic acid and their derivatives (esters, amides, nitriles) were obtained for a first time. Mentioned synthetic protocols were based on alkylation of proper potassium thiolates and thions. The possibility of interconversion of functional derivatives of 2-[(3-R-8-R1-9-R2-10-R3-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazolin- 6-yl)thio]acetic acid, which may be used as preparative methods was showed. Linear correlational relationships “structure –anticancer activity” for series of N-R-2-[(3-R-8-R1-9-R2-10-R3-2-oxo-2Н-[1,2,4]triazino[2,3-c]quinazoline-6-yl)-thio]acetamides was established for a fist time, QSAR models which allowed to conduct in silico screening of combinatorial libraries and purposeful synthesis of compounds with high anticancer action. The spectral characteristics (1Н та 13С NMR-, IR-, mass-spectra) of halogen-containing 3-R-8-R1-9-R2-10-R3-6-thioxo-6,7-dihydro-2-oxo-2Н-[1,2,4]triazino-[2,3-с]quinazolin-2-ones and 2-[(3-R-8-R1-9-R2-10-R3-2-oxo-2H-[1,2,4]triazino-[2,3-c]quinazolin-6-yl)thio]acetic acid and their functional derivatives were described. Non-typical signal of remote from chiral carbon atom SCH2CO fragment as two doublets with coupling constant 18.6-15.9 Hz were shown. Conducted assays for biological action of halogen-containing 3-R- 8-R1-9-R2-10-R3-6-thioxo-6,7-dihydro-2-oxo-2Н-[1,2,4]triazino[2,3-с]quinazolin-2-ones and 2-[(3-R-8-R1-9-R2-10-R3-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazoline-6-yl)thio]acetic acid and their derivatives (esters, amides, nitriles) using «in silico», «in vitro» and «in vivo» models allowed to reveal “lead-compounds” with high actoprotective, cerebroprotective, antibacterial, anticancer and antiviral activity. It was shown, that soluble in water sodium 2-[(3-R-2-oxo-2Н-[1,2,4]tria-zino[2,3-с]quinazolin-6-yl)thio]acetates revealed actoprotective and cerebro-protective action and compound 8.1 in dosage 10 mg/kg increase the blood supply of the brain of intact animal without any effects on arterial tension. It was shown that S-substituted 3-R-8-R1-9-R2-10-R3-6-thioxo-6,7-dihydro-2Н-[1,2,4]triazino[2,3-с]quinazolin-2-ones, which inhibited bioluminescence of Photobacterium leiognathi Sh1 also revealed high activity against St. aureus and antifungal action against C. аlbicans. It was estimated, that 2-[(3-R-9-R1-10-R2- 2-oxo-2Н-[1,2,4]triazino[2,3-с]quinazolin-6-yl)thio]acetamides with fragment of carcass amines revealed antiviral activity which were comparable to action of «Ribavirine». For the first time experimental confirmation of CK2-protein kinase inhibiting action of N-R-2-[(3-R-8-R1-9-R2-10-R3-2-oxo-2Н-[1,2,4]triazino[2,3-c]quinazolin-6-yl)thio]acetamides was showed. Mentioned ability may be considered as possible mechanism of anticancer, what opened up a new chapter in the searching of the novel antitumor agents among quinazolines and its condensed derivatives. Розроблена та реалізована стратегія пошуку хіміотерапевтичних засобів, що передбачає використання методології in silico скринінгу, в рамках якої син-тезовано ряд 2-[(3-R-8-R1-9-R2-10-R3-2-оксо-2Н-[1,2,4]триазино[2,3-c]хіназолін-6-іл)тіо]оцтових кислот та їх функціональних похідних, для яких досліджено фізико-хімічні та біологічні властивості. Встановлені можливості та обмеження модифікації 3-R-8-R1-9-R2-10-R3-6-тіоксо-6,7-дигідро-2H-[1,2,4]триазино[2,3-c]хіназолін-2-онів та їх S-калієвих солей з метою введення до складу зазначеної гетероциклічної системи відомих фармакофорних фрагментів за допомогою ацетамідної «лінкерної» групи. На основі результатів біологічних досліджень встановлено перспективність пошуку протипухлинних, протигрибкових, противірусних, актопротекторних та церебропротекторних агентів серед синтезованих сполук та ідентифіковані «сполуки-лідери». Встановлені лінійні кореляційні взаємозв’язки «структура-протипухлинна активність» в ряду N-R-2-[(3-R-8-R1-9-R2-10-R3-2-оксо-2Н-[1,2,4]триазино[2,3-c]хіназолін-6-іл)тіо]ацетамідів та розроблені QSAR-моделі, що дозволило провести in silico скринінг комбінаторних бібліотек і спрямований синтез сполук із значним протипухлинним потенціалом, який підтверджено експериментально. Вперше для N-R-2-[(3-R-8-R1-9-R2-10-R3-2-оксо-2Н-[1,2,4]триазино[2,3-c]-хіназолін-6-іл)тіо]ацетамідів одержано експериментальне підтвердження реалізації протиракової активності шляхом інгібування протеїнкінази СК2, що відкриває шлях до подальшого системного вивчення хіназолінів та їх анельованих аналогів як потенційних лікарських засобів в терапії онкозахворювань
Synthesis, physico-chemical and biological properties of 2-[(3-R-2-оxo-2Н-[1,2,4]triazino[2,3-c]quinazolin-6-yl)thio]acetic acids and then substituted
Keywords: синтез; галогеновмісні 6-R-3-(2-аміно-3-R1-4-R2-5-R3-феніл)-1,2,4-триазин-5-oнів; калій 3-R-8-R1-9-R2-10-R3-2-оксо-2Н-[1,2,4]-триазино[2,3-с]хіназолін-6-тіолати; 2-[(3-R-8-R1-9-R2-10-R3-2-oксо-2H-[1,2,4]-триазино[2,3-c]-хіназолін-6-іл)тіо]оцтові кислоти та їх функціональні похідні; спектральні характеристики; фармакологічний скринінг; синтез; галогеносодержащие 6-R-3-(2-амино-3-R1- 4-R2-5-R3-фенил)-1,2,4-триазин-5-oны; калий 3-R-8-R1-9-R2-10-R3-2-оксо-2Н-[1,2,4]триазино[2,3-с]хиназолин-6-тиолаты; 2-[(3-R-8-R1-9-R2-10-R3-2-oксо-2H-[1,2,4]триазино[2,3-c]хиназолин-6-ил)тио]уксусные кислоты и их функциональные производные; спектральные характеристики; фармакологический скрининг; synthesis, halogen-containing 6-R-3-(2-amino-3-R1-4-R2-5-R3-phenyl)-1,2,4-triazin-5-ones; potassium 3-R-8-R1-9-R2-10-R3-2-оxo-2Н-[1,2,4]-triazino[2,3-с]quinazolin-6-thiolates; 2-[(3-R-8-R1-9-R2-10-R3-2-oxo-2H-[1,2,4]-triazino[2,3-c]quinazolin-6-yl)thio]acetic acids and their functional derivatives; spectral data; pharmacological screening